2008
DOI: 10.1055/s-2008-1034317
|View full text |Cite
|
Sign up to set email alerts
|

Ampelopsin Prevents Apoptosis Induced by H2O2 in MT-4 Lymphocytes

Abstract: Human immunodeficiency virus (HIV) infection can result in oxidative stress through production of reactive oxygen species (ROS). Simultaneously, oxidative stress is able to activate the replication of virus and lead to the apoptosis of T lymphocytes which is the defense of the immune function. Ampelopsin, belonging to the flavonoids, is a purified component from the root of a Chinese medicinal herb. Our previous studies revealed that ampelopsin could protect sensitive cells against HIV-1 infection and reduce H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…DMY displays many pharmacological activities, such as anti-inflammatory, cough relieving, antimicrobial, anti-hypertensive, antioxidative, hepatoprotective, and anti-carcinogenic effects (Daoud et al, 2014;Guo et al, 2014;Radhakrishnakartha et al, 2014;Zhu et al, 2014). Recently published data support the notion that DMY, as an antioxidant, protects PC12 and MT-4 cells against oxidative injury (Ye et al, 2008;Zou et al, 2014). The existing literature confirmed that DMY upregulates the level of phosphorylated AMPK (p-AMPK) in a doseand time-dependent manner (Xia et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…DMY displays many pharmacological activities, such as anti-inflammatory, cough relieving, antimicrobial, anti-hypertensive, antioxidative, hepatoprotective, and anti-carcinogenic effects (Daoud et al, 2014;Guo et al, 2014;Radhakrishnakartha et al, 2014;Zhu et al, 2014). Recently published data support the notion that DMY, as an antioxidant, protects PC12 and MT-4 cells against oxidative injury (Ye et al, 2008;Zou et al, 2014). The existing literature confirmed that DMY upregulates the level of phosphorylated AMPK (p-AMPK) in a doseand time-dependent manner (Xia et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…It was reported that the DHM can reach more than 30% in the tender stem and leaves of vine tea [1]. DHM has numerous pharmacological activities, such as anti-inflammatory, relieving cough, antimicrobial activity, anti-hypertension, anti-oxidation, hepatoprotective effect and anti-carcinogenic effect [2][5]. Recently, plenty of data supported that DHM could inhibit the growth and metastasis of prostate cancer in vitro and in vivo [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among six isolated compounds, compound 1 exhibited higher activity with IC 50 value of 2.6 μg/ml than vitamin C, used as a positive control (IC50 value, 6.4 μg/ml) (Table IV). It was reported that compound 1, ampelopsin has protective effect on oxidant stress-induced apoptosis induced by H2O2 in MT-4 cells, antitumor effects, inhibitory effects on angiogenesis, and hepatoprotective activity (Murakami et al, 2004;Zeng et al, 2004;Luo et al, 2006;Ye et al, 2008). The results from free radical scavenging systems revealed that the ethyl acetate soluble fraction of S. koreana, and isolated compounds 1-3 may be useful for the treatment of various oxidative damage.…”
Section: Resultsmentioning
confidence: 99%